PERAN KONSELOR LINTAS AGAMA DAN BUDAYA SEBAGAI PROBLEM SOLVING MASYARAKAT MULTIBUDAYA [THE ROLE OF CROSS-RELIGIOUS AND CULTURAL COUNSELORS AS A MULTI-CULTURAL COMMUNITY SOLVING PROBLEM] - Zakiyah, Afifatuz; Rahmat, Hayatul Khairul; Sa'adah, Nurus (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2022)
This research is motivated because the condition of Indonesia as a country that is rich in culture, of course, results in different patterns of life in society, so it is necessary to have a facilitator who can facilitate the unrest of the community. Therefore, this study aims to determine the role of interfaith and cultural counselors as problem solving in a multicultural society. This research uses a literature study approach. Sources of data that will be used as material for this research are books, journals, and internet sites related to the chosen topic. In this study, after the data was collected, the data was analyzed to get a conclusion. The results of this study are that religious and cultural sensitive counselors are counselors who must have awareness in knowing their own culture in all respects. Therefore, it is understood that what can influence the mindset, actions and feelings of a counselee can come from every culture. A counselor must be able to find the right approach or according to the characteristics of the counselee and should not force the counselee to follow the cultural values that the counselor wants. Therefore, the role of the counselor must really understand the characteristics of the counselee in terms of religion and culture.